The effect of guia exame’s ratings on the Brazilian fund industry: an analysis of net-worth flows - Eid Júnior, William (2006)
This paper infers the impact the publication “Guia Exame” (the guide) has on the Brazilian fund industry, more specifically on the ability the concerned funds develop on attracting new investment. The impact is measured using the event-study analysis based on the variation of net worth subsequently to the event of being rated, according to the methodology applied by the guide to rank the funds. We used five years of fund ratings according to Guia Exame (2000-2004) and analyzed the changes of these funds’ net worth. We also compared the event amongst different categories of funds. The results found confirm the expected effects according to star rankings and asset manager size in all years.